The State's Efforts to Realize Boum Publicum Through Preventing the Occurrence of Corruption Crimes - Azistasari, Sandita; Septaviana, Diana (RechtIdee, 2024)
Recently, corruption in Indonesia has been rampant. Corruption announcements are often found in every media (television, news, or social media). One of the cases that attracted enough attention from the public is the corruption against COVID-19 social aid committed by The Minister Of Social Department, Juliari Batubara, for Rp 32.4 billion. In conclusion, corruption is spreading to most of the country and involving more actors, which describes the irony of decentralization and democracy. Therefore, most of the corruption in countries was done by placemen who citizens elected. This irony should be able to open Indonesian eyes to the deterioration of human resources. As a citizen and future generation who were desperately hoping for the progress of our beloved country, then we did a case study related to the corruption against COVID-19 social aid that was committed by The Minister of Social Department, which later we arranged in a simple journal, in the hope this journal able to provide readers’ understanding that corruption can conduce not only state detriment but also a deterioration of human resources. This research is a juridical research. The problem approach uses a statutory approach and a conceptual approach. The technique of collecting legal materials uses library research.